Intellectual Property Rights Relating to Integrated Circuit Layout Design: India, Bangladesh, and United States Perspectives - Yana Priyana (The Easta Journal Law and Human Rights, 2022)
The purpose of this study is to discuss the current situation of legal protection of integrated circuit layout design, to identify various international legal instruments on integrated circuit layout design and to highlight the need and importance of the entry into force of a new law on integrated circuit layout. Secondary sources have been used in this study. The research method used in this study is a type of qualitative research as a research procedure which produces descriptive data in the form of written and spoken words of individuals or groups as well as observable behavior. In this case to research and find specifics about Intellectual Property Rights Related to Integrated Circuit Layout Design: India, Bangladesh and United States Perspectives. The writing uses a quantitative research approach. The focus of the research is Intellectual Property Rights and Layout Design of Integrated Circuits. Piracy of layout designs of Integrated Circuits is a very common issue in most cases in Bangladesh. Intellectual property protection is not up to standard in Bangladesh, causing many violations. This is because the laws related to IPR in Bangladesh are still very premature and few in number. That's why most IP rights cannot be protected. There are no special provisions for the protection of integrated circuit layout designs. As integrated circuit layout design is at an early stage in Bangladesh, it is important for the country to promote strong protection policies by enacting the Integrated Circuit Layout Design Act. The number of Bangladeshi companies focusing on integrated circuit layout design is starting to grow and this will force large semiconductor companies to set up their offices and cater to the needs of the domestic market. This will encourage more companies to base their operations in Bangladesh.